How School Culture Reacts to Change in the Context of Primary Education in Greece - Chalkiadaki, Areti; Tomás-Folch, Marina (International Journal of Education, 2020)
The purpose of this paper is to study the predisposition of school culture to the introduction of change in teaching practices, as this is dictated by the conditions of the 21st century. The conceptual areas discussed include the introduction and implementation of change and innovation in education, 21st century skills and school culture. Since the research primary data was collected in the Greek educational system, the characteristics of the specific context are also analysed. The research methodology develops on a pragmatic basis, combining quantitative and qualitative research methods, namely semi-structured interviews, a survey, and document analysis, within a sequential three-stage design. The development of the research tools and the data analysis is conducted with reference to an originally designed model of four school culture types. The results point to an actual school culture that combines both change negative and change positive characteristics. Specific aspects are evaluated as more change negative school culture characteristics, such as the families’ role and the approach to the development of the personal, social and civic skills, while others as more change positive ones, such as school management.